A spectrophotometric method for the determination Co-EDTA complexes - Paraneeiswaran, Arunachalam; Shukla, Sudhir K; Sathyaseelan, V.S.; Rao, Toleti Subba (International Journal of Applied Sciences and Biotechnology, 2015)
A precise quantification of Co(II)EDTA complex is required to develop bioremediation approaches for Co(III)EDTA complex that is generated in various industrial processes. It is cumbersome to quantify Co(II)EDTA in a mixture of Co(II)EDTAand Co(III)EDTAby normal UV-visible spectrophotometric methods as both the complexes absorb significantly at 490 nm, which is the λ max of Co(II)EDTA. Whereas other sophisticated techniques such as gas chromatography, atomic absorption spectrophotometer, inductively coupled plasma-atomic emission spectroscopy can measure individual species of Co(II)EDTA or Co(III)EDTA when present alone but are ineffective to measure the Co(II)EDTAprecisely when it is mixed with Co(III)EDTA. Hence, an attempt has been made to develop a spectrophotometric method for its quantification. This paper describes the development of a simple and economic dual wavelength spectrophotometric method for the determination of Co(II)EDTAin a mixture of Co(II)EDTA and Co(III)EDTA complexes. The wavelength pair, 490-580 nm was optimized for the measurement of absorbance for this dual wavelength method of determination of Co(II)EDTA in the presence of Co(III)EDTA. Int J Appl Sci Biotechnol, Vol 3(4): 584-587